Exploratory cases on the interplay between green human resource management and advanced green manufacturing in light of the Ability-Motivation-Opportunity theory - Jing*, Yi Yong; Yusliza, M.Y.; Jabbour, Charbel Jose Chiapetta; Noor Hazlina, Ahmad (Emerald Publishing Limited, 2019)
Purpose Green human resource management (HRM) has been considered to be a vitally important mechanism for companies to move towards a sustainable organization. By adopting the Ability-Motivation-Opportunity as the underpinning theory, the purpose of this paper is to identify the factors that facilitate the adoption of Green HRM in Malaysia.